Computer-aided screening of marine fungal metabolites as potential inhibitors of new Delhi metallo-beta-lactamase-1 - Shabbir, Farhat; Mishra, Vipin Kumar; Noor, Sana; Nath, Subrata; Khan, Muhammad Umer; Fawy, Khaled Fahmi; Nishan, Umar; Dib, Hanna; Shah, Mohibullah; Chen, Ke (Scientific reports, 2025)
New Delhi metallo-beta-lactamase-1 (NDM-1) is a protein produced by bacteria carrying the blaNDM-1 gene, leading to antibiotic resistance, a major global health issue. NDM-1 hydrolyzes nearly all beta-lactam antibiotics, including last-resort carbapenems. Developing effective NDM-1 inhibitors is crucial, as none are currently available for clinical use. This study investigates the potential anti-NDM-1 effects of reported marine fungi-derived metabolites. Two hundred metabolites of fungal origin with antibacterial activity were collected and virtually screened targeting key active site residues of NDM-1. We examined the drug-likeness characteristics, interaction profile, and pharmacophoric features of the shortlisted metabolites followed by molecular dynamic (MD) simulation: RMSF, RMSD, Rg, SASA, hydrogen bond analysis, MMGBSA, PCA, and FEL. Fifty-eight metabolites exhibited greater binding affinity than the reference drug (meropenem) with the highest score of -6.59 kcal/mol. The top 7 metabolites were selected for interaction analysis based on drug-likeness criteria. The diverse interactions of our top metabolites with key residues (HIS-122, GLN-123, GLU-152, and ASN-220) suggest potential NDM-1 inhibition and disruption of bacterial resistance. Pharmacophoric features highlighted the effective structural characteristics of the top 3 metabolites. Three metabolites namely, 8-O-4-dehydrodiferulic acid, Emerixanthone B, and Trichaspside B demonstrated favorable dynamic behavior and binding stability, with 8-O-4-dehydrodiferulic acid showing the most promising potential. Furthermore, the top metabolites are non-toxic, compatible with β-lactam antibiotics, and show no predicted interactions with human proteins. These selected compounds exhibit favorable physiological compatibility and molecular characteristics that enhance their potential as therapeutic candidates. Given the urgent need for novel treatments targeting NDM-1, the investigated metabolites warrant further experimental validation.